Performance analysis of 2015 FIFA Women’s World Cup Champion USA National Team - Aydin Senturk; Gizem Baskaya (Türk Spor ve Egzersiz Dergisi)
This study was performed in order to analyze 2015 FIFA Women’s World Cup Winner U.S.A. National Team, in terms of different variables. Data were obtained from FIFA (Federation Internationale de Football Association) official web site. Technical parameters such as the distribution of the goals scored in terms of time intervals, ball possession percentage for first half and whole matches, the number of shots, the number of shots on target, corner kicks, off sides, and some other parameters such as the considering the rights of player substitutions were analyzed. Obtained data were recorded in SPSS 17 packaged software, then frequency and percentage figures were calculated and interpreted. Age average was 30.35 ± 4.42, total goals scored were 14, goal average was 2.00 per match, and three own goals with 0.27 goal average per match, these were some results determined. Based on time intervals, U.S.A Team goal percentages were; 42.86% (6 goals) of total 14 goals in first half, 57.14% (8 goals) of total 14 goals in second half; 66.7% (2 goals) of goals in its own net in first half, 33.3% (1 goal) in second half and own goal. Shot average was 13.9 per match and ball possession percentage was 52.86%.